التوجه نحو التدين لدى المتربصين دراسة ميدانية بمعهد التعليم المهني كريم بلقاسم بالأغواط (El-Wahat Journal for Research and Studies, 2020)
The Aim Of  Study Was  Identify The Level Of Attitudes  Towards Religiosity Among The Trainees At The Institute Of Vocational Education Krim Belkacem In Laghouat And Its Relationships With Some  Variables.The Study Concluded That:• The Level Of Attitudes Towards Religiosity Among Trainees At The Vocational Education Center Karim Belkacem Is High.• There Is A Positive Correlation Relationship Between The Trend Towards Apparent Religiosity And The Attitudes Towards Fundamental Religiosity Among The Trainees At The Center For Vocational Education• There Are Statistically Significant Differences In The Orientation Towards Religiosity Among The Trainees At The Vocational Attributed To The Gender Variable In Favor Of Females.• There Are No Statistically Significant Differences In The Attitudes Towards Religiosity Among The Trainees At The Vocational Education Center Due To The Age Variable.• There Are No Statistically Significant Differences In The Attitudes Towards Religiosity Due To The Variable Of The Academic Level. Key Words- Attitudes, Religiosity, The Trainees